Characterization of the Localized Agri-Food System (SYAL) for the Andean blueberry (Vaccinium meridionale Swartz) in the Boyaca Department, Colombia - Quevedo-Rubiano, Santiago; Aranda-Camacho, Yesid; Ligarreto-Moreno, Gustavo Adolfo; Magnitskiy, Stanislav (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The Andean blueberry (Vaccinium meridionale Swartz), known locally as agraz, possess a high level of anthocyanins and antioxidants and represents a socio-economical, environmental, and cultural alternative in Colombia. However, a characterization of the agri-food system has been done, limiting strategies for its valorization. The objective of this study was to characterize the Localized Agri-food System (SYAL) of the Andean blueberry in the Occidente and Ricaurte provinces of the Boyaca Department of Colombia. Three analytical axes were used within the SYAL approach: territorial anchorage, activation processes, and links between product quality and territory. The farmer product circuit methodology was used to identify agents linked to the product commercialization chain in the territory, and their participation was estimated. Data treatment was performed with descriptive statistics and multivariate analysis, specifically principal component analysis for numerical variables and multiple correspondence analysis for categorical variables. A SYAL was evident in the early stages of consolidation, with exceptional adaptations to the biophysical conditions in the territory. Finally, four groups of actors were identified, where the main discriminating variable was membership in an organization of farmers, a determining condition for business competitiveness in the territory.